Knowledge, attitude and behaviour towards dietary salt intake among adults’ residents of sub-urban setting in Kuantan - Pasi, Hafizah; Ab Rahman, Jamalludin; Mohd Rus, Razman; Abd. Aziz, Karimah Hanim; Nasreen, Hashima E; Yusof, Muhammad Zubir (2017)
Background: Non-communicable diseases, especially salt-related ones such as hypertension are on the rise in today’s society. As such, this study was undertaken to explore the knowledge, attitude and behavior towards dietary salt intake as well as any possible relation between their socio-demographic statuses and health of adult resident in a sub-urban housing area in Kuantan, Pahang. Methodology: A cross-sectional study design was conducted, involving 239 consenting adult respondents. An interview-guided questionnaire was administered to all the participants to assess their knowledge, attitude and behavior towards dietary salt intake and its effects on health. Results: 98.7% of the respondents have poor level of knowledge. Curiously, 87% of the respondents have favorable attitude and the mean behavior score of the respondents was 5.92 (SD=2.22) which was good. There was no significant relation of socio-demographic characteristics or health status with the level of knowledge or attitude. There was however a significant relationship between age as well as gender with the behavioral practices. Conclusion: We found that the majority of our population had poor knowledge but exhibited a fairly good attitude and behavior towards dietary salt intake. It is also important to note that female and adults in the 35 to 50 years old had better behavior. Therefore, the government needs to put greater effort in promoting the National Salt Reduction Strategy to educate the society, improve their practices as well as to pressure more food industries to produce healthier food options for Malaysians.